Materials to the creation of the Regional Landscape Park ‘Smarahdove Dzherelo’ (Kharkiv Region, Ukraine) - Atemasova, Т.; Atemasov, A.; Viter, S.; Gamulya, Yu.; Drogvalenko, O.; Polchaninova, Н.; Prylutsky, O.; Sinna, O.; Terekhova, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2021)
Intending to create a regional landscape park, we investigated various sites of upland oak forests, pine forests on the above-floodplain terrace of the left bank of the Udy River, adjacent floodplain meadows on both banks, and swampy soil depressions near the village of Ternovaya. In total, we proposed seven segments with a total area of ​​6173.03 hectares to be included in the Smarahdove Dzherelo Regional Landscape Park, a projected conservation area in the south of the Kharkiv District of the Kharkiv Region. The studied oak forests on the right river bank and flat interfluves, pine forests on the above-flooded terrace, and the Udy floodplain are examples of the typical landscape of Slobidska Ukraine. The Udy floodplain hosts meadows of a significant area and alder forests in humid near-terrace depressions; dry meadows are confined to forest edges and fallow lands. In total, ten endangered natural habitats listes in the Berne Convention are presented in the study area. Flora and vegetation are rich and, in general, retain the composition inherent in the biotopes of the southern forest-steppe of Left-Bank Ukraine. One plant association is included in the Green Book of Ukraine; the other three are in the List of Rare Plant Associations of the Kharkiv Region. Five vascular plant species, one fern species, and one fungus species are included in the Red Data Book of Ukraine; 14 plant species are included in the Red List of the Kharkiv Region. We found eight animal species of the European Red List, 65 animal species from Appendices II and III of the Bern Convention, including six species from Appendices I and II of the Bonn Convention; 23 animal species are included in the Red Data Book of Ukraine, while 19 species are in the List of Rare Species and Species in Need of Protection in the Kharkiv Region. New locations of species requiring protection at the regional and all-Ukrainian level have been identified. Species at the boundaries of their ranges make a significant contribution to local biodiversity. Several southern species were found on the dry edges of the Chornyi Lis forest area: for the Mantis Iris polystictica, it is the second record from the Kharkiv Region, for the spiders Marinarozelotes malkini and Ero aphana, it is the first record in the regional list. Two beetle species (Fissocatops westi and Scymniscus horioni) are new to the fauna of Ukraine. We assessed the degree of preservation of natural communities and the possibility of their inclusion in various zones of the projected regional landscape park. Basic biotechnical measures were recommended to maintain the natural properties of the park ecosystems.